Review—The Application of an Electro-Peroxone Process in Water and Wastewater Treatment. Issue 6 (1st January 2017) - Turkay, Ozge; Ersoy, Zeynep Girgin; Barışçı, Sibel
Abstract : The objective of the present study is to describe a novel electro-peroxone (E-peroxone) process as a combination of two different systems for hydroxyl radical generation—ozonation and electrolysis—and to highlight its advantages for water and wastewater treatment compared to each system alone. An extensive review on the mechanism of the production of hydroxyl radical and in-situ generation of hydrogen peroxide, and the kinetics and efficiency of E-peroxone has been performed to evaluate the degradation and mineralization of different kinds of pollutants in aqueous media. The effects of experimental parameters such as ozone dose, applied current, solution of pH, anode type, and cathode selection on the efficiency of E-peroxone are discussed.